C mara de ionización para espectrometría alfa - Bonard, R.T.; Lara Manning, Mauricio; Gayoso, R.A.P.; Dupetit, G.A. (Comisión Nacional de Energía Atómica (CNEA), 1962)
Fil:Bonard, R.T. Comisión Nacional de Energía Atómica (CNEA). República Argentina